2017
DOI: 10.21887/ijvsbt.v13i02.10055
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Canine Parvo Viral Infection in Dogs in and around Navsari District of Gujarat State, India

Abstract: A total of 145 faecal samples were collected from the dogs suspected for canine parvovirus (CPV) infection over a period of one year from April, 2016 to March, 2017. The faecal samples were screened by HA, Scan Vet Parvo kit and PCR. Out of 145 dog faecal samples screened, 63 samples were positive with an overall prevalence of 43.44 %. Breed wise analysis of data indicated higher prevalence in indigenous breeds (46.67%) than the exotic breeds (42.00%). CPV infection in relation to age was highest (54.05%) in 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Also, mostly male dogs were kept for breeding purposes by a greater percentage of population (Deka et al, 2013;Thomas et al, 2014) [7,36] . Season wise incidence of CPV was found to be highest in spring 86/258 (33.33%) and winter 75/258 (29.07%) respectively, followed by Autumn 53/258 (20.54%) and least in Summer 53/258 (17.05%) which is supported by findings of Mehta et al, (2017) [18] who noted higher prevalence during the winter season (58.67%) followed by summer (37.50%) and the least in monsoon (18.42%) season (Table 2) (Figure 5). This might be due to the ensuing of more whelping during the time period of November and December.…”
Section: Resultssupporting
confidence: 71%
“…Also, mostly male dogs were kept for breeding purposes by a greater percentage of population (Deka et al, 2013;Thomas et al, 2014) [7,36] . Season wise incidence of CPV was found to be highest in spring 86/258 (33.33%) and winter 75/258 (29.07%) respectively, followed by Autumn 53/258 (20.54%) and least in Summer 53/258 (17.05%) which is supported by findings of Mehta et al, (2017) [18] who noted higher prevalence during the winter season (58.67%) followed by summer (37.50%) and the least in monsoon (18.42%) season (Table 2) (Figure 5). This might be due to the ensuing of more whelping during the time period of November and December.…”
Section: Resultssupporting
confidence: 71%
“…The lower CCoV prevalence in our study concludes that CCoV does not prevail as CPV is, in south Gujarat, as there is no past reports from this region on prevalence of CCoV, whereas CPV is endemic in south Gujarat as reported by Mehta et al (2017), Pandya et al (2017) and Sharma et al (2018). LFA test is rapid, quick, simple, usable and comparatively inexpensive at the field level, which make it the first choice of clinical support at the field and veterinary dispensaries for diagnosis.…”
Section: Results a N D Discussionmentioning
confidence: 47%
“…Similar findings were reported by Al-Bayati et al (2010) [1] who reported high prevalence during September-December months. This could be due to the survivability and growth of virus in cold climate as opined by Mehta et al (2017) [12] . However contradictory to these findings reported by Mohammed et al (2005) [13] who reported highest prevalence in May to June months.…”
Section: Resultsmentioning
confidence: 98%